Adolescent Developmental Stressors: Emotional Intelligence as a Moderator of Psychosocial Wellbeing - Khalkho, Rajiv (Journal of Research in Vocational Education, 2025)
Adolescent stress is on the rise, affecting relationships (role stress), life purpose (existential stress), emotional intelligence, and wellbeing. Research on role stress and existential stress has largely focused on adults, with assumptions that they have wider social interactions and multiple role identities. This explanatory sequential mixed - methods research aims to fill this gap by exploring adolescents' experiences of role and existential stress, and how these stressors influence their emotional intelligence and wellbeing in educational settings. A total of 375 adolescents, aged between 13 - 19 years, from Year 8–12 participated in an online survey, which included four scales: the Role Stress Scale, Purpose in Life Test, Brief Emotional Intelligence Scale, and Perceived Wellness Survey. Out of 365 participants, 165 were males and 210 were females from local schools in Adelaide, South Australia. Semi - structured interviews were conducted with 9 adolescents (6 females and 3 males) who reported high or low role and existential stress. The findings revealed a bi - directional relationship between these constructs. Participants with low role and existential stress reported positive, supportive family relationships, which seemed to provide a foundation for other relationships, likely because social skills for building and maintaining relationships were modelled in the family context. This research contributes to the field by offering insights into the impact of stress on adolescents' emotional development and suggests implications for educational practice, policy, and future research across diverse international contexts.